Hepatorenal protective effects of essential oils against chemical overexposure induced oxidative damage - Jiang, Faming; Huang, Xiaoyan; Chen, Xingying; Xian, Yuanhua (Frontiers in Pharmacology, 2025)
Chemical overexposure is a significant concern in both environmental and occupational settings, often leading to oxidative stress and subsequent cellular damage. The review covers the oxidative stress induced by chemical overexposure to substances such as pesticides (including pyrethroid, deltamethrin, β-cyfluthrin, malathion, triflumuron, methomyl, diquat, cypermethrin, thiamethoxam, and profenofos), medications (acetaminophen), nanoparticles (including zinc oxide, iron, silver, and titanium dioxide), heavy metals (including cadmium, vanadium), and some organic chemicals (including diethylnitrosamine and benzo(a)pyrene). Focusing on preclinical evidence from animal models and cell-based studies, essential oils have been shown to significantly enhance antioxidative enzyme activities, including superoxide dismutase, catalase, and glutathione peroxidase, while also increasing levels of non-enzymatic antioxidants such as glutathione and uric acid. Additionally, essential oils contribute to the restoration of biochemical parameters, including creatinine, uric acid, and urea levels, while mitigating oxidative damage by reducing cell membrane injury, apoptosis, and histopathological alterations. Additionally, this review evaluates the protective benefits of essential oils against chemical overexposure in animal models. The underlying mechanism is involved in alleviating hepatorenal damage. This review underscores the considerable promise of essential oils as candidates for medicinal applications in functional foods or medicines, particularly in preventing oxidative stress induced by various chemical overexposure.